Derrida e la testimonianza come esperienza impossibile e necessaria - Perego, Vittorio (Teologia, 2020)
Derrida's philosophy cannot be relegated to a mere expression of postmodern nihilism, especially in the Anglo-Saxon debate the adoption of the deconstructionist perspective in the biblical studies and in theological reflection is now consolidated. The aim of this article is to present the figure of the witness in Derrida, starting from the structure of the experience brought to light by the French philosopher in his first phenomenological studies. Husserl's analyses of temporality and alter ego reveal the impossible presence to itself: consciousness is always contaminated and solicited by an instance, which can never be reduced to its concept. The meaning in fact is constituted through the way in which the singularity inscribes this instance in its historical horizon. The witness is configured as a necessary experience, because without its mediation the meaning would not appear, but also impossible, because it is presented as the way in which the self responds to the promise of fulfilment always to come.